Target‐site mutations Ile1781Leu and Ile2041Asn in the ACCase2 gene confer resistance to fluazifop‐p‐butyl and pinoxaden herbicides in a johnsongrass accession from Arkansas, USA - Fidel González‐Torralva; Jason K. Norsworthy (Plant Direct)
Abstract Johnsongrass [Sorghum halepense (L.) Pers.] is a troublesome weed species in different agricultural and non‐agricultural areas. Because of its biology, reproductive system, and seed production, effective management is challenging. An accession with low susceptibility to the acetyl‐CoA carboxylase (ACCase)‐inhibiting herbicides fluazifop‐p‐butyl (fluazifop) and pinoxaden was collected in eastern Arkansas. In this research, the molecular mechanisms responsible for ACCase resistance were investigated. Dose–response experiments showed a resistance factor of 181 and 133 for fluazifop and pinoxaden, respectively. Molecular analysis of both ACCase1 and ACCase2 genes was researched. Nucleotide comparison of ACCase1 between resistant and susceptible accessions showed no single nucleotide polymorphisms. Nonetheless, analysis of ACCase2 in fluazifop‐resistant johnsongrass plants revealed the Ile1781Leu target‐site mutation was dominant (nearly 75%), whereas the majority of pinoxaden‐resistant johnsongrass plants had the Ile2041Asn (60%). Not all sequenced johnsongrass plants displayed a target‐site mutation, suggesting the presence of additional resistance mechanisms. Amplification of ACCase1 and ACCase2 was not responsible for resistance because of the similar values obtained in both resistant and susceptible accessions. Experiments with malathion and NBD‐Cl suggest the presence of herbicide metabolism. Outcomes of this research demonstrated that fluazifop‐ and pinoxaden‐resistant johnsongrass plants displayed a target‐site mutation in ACCase2, but also that non‐target‐site resistance mechanisms would be involved and require a detailed study.